Comparison of Productivity and Physiological Traits of Faba Bean (Vicia faba L.) Varieties under Conditions of Boreal Climatic Zone - Daiva Janusauskaite; Kristyna Razbadauskiene (Agronomy, 2021)
This study aimed to evaluate and compare the physiological traits, productivity, and seed quality of nine faba bean varieties grown in a field trial under the Boreal climate conditions. A two-factor field experiment was laid out in a split-plot design: The seeds in the main plots were sown and treated with seed fungicide (SF) and untreated (without SF) (factor A). The sub-plots were assigned to nine varieties (factor B). The physiological traits of faba bean significantly varied among the varieties, and the behavior of faba bean varieties differed between the two growing seasons. The values of physiological traits for varieties Julia and Boxer significantly surpassed the trial mean under wet conditions, while the trait values for Fuego and Bioro were surpassed under conditions of a lack of moisture. Fungicidal seed treatment had a negligible effect on the physiological traits, while it had a significant negative influence on the leaf area index at the beginning of the flowering stage. SF had a noticeable effect on seed yield only for the varieties Nida DS and Fuego. The findings of the study revealed that Fuego and Isabell were the most suitable faba bean varieties for cultivation in the Boreal climate zone as they were distinguished from the other tested ones by the highest seed yields.